2018
DOI: 10.1002/ajoc.201800250
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent N‐Heteroarenes Having Large Stokes Shift and Water Solubility Suitable for Bioimaging

Abstract: A series of fluorescent dimeric imidazo[1,5‐a]pyridinium salts have been synthesized. These salts displayed large Stokes shifts (up to 196 nm), possessed good water solubility, and exhibited blue to yellow emission (Φem=up to 0.50) in solution. When one specific compound was used for co‐incubation of HeLa cells, green fluorescent signals were observed. The combined use of the salt and commercially available blue fluorescent dye realized the double staining of HeLa cells under the single UV excitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Monovalent organic cations, where size, shape and electronic structure can be varied over wide limits, are a valuable tool for introducing useful properties into the hybrid structure. Heterocycles with the imidazo[1,5-a]pyridine skeleton have been identified as highly emissive fluorophores that render them suitable for optoelectronic devices (Hutt et al, 2012;Yagishita et al, 2018). Incorporation of the imidazo[1,5-a]pyridinium moiety in the hybrid structure is ISSN 2056-9890 expected to extend the applications of the organic material, and also address such issues as mechanical properties, chemical resistance, thermal stability, etc., that limit the applicability of pure organics.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Monovalent organic cations, where size, shape and electronic structure can be varied over wide limits, are a valuable tool for introducing useful properties into the hybrid structure. Heterocycles with the imidazo[1,5-a]pyridine skeleton have been identified as highly emissive fluorophores that render them suitable for optoelectronic devices (Hutt et al, 2012;Yagishita et al, 2018). Incorporation of the imidazo[1,5-a]pyridinium moiety in the hybrid structure is ISSN 2056-9890 expected to extend the applications of the organic material, and also address such issues as mechanical properties, chemical resistance, thermal stability, etc., that limit the applicability of pure organics.…”
Section: Chemical Contextmentioning
confidence: 99%
“…They also show strong fluorescence intensity and high quantum yield. 17–19 Encouraged by the successful incorporation of the imidazo[1,5- a ]pyridinium moiety in the halometallate structure that produced the fluorescent [L] 2 [ZnCl 4 ] hybrid salt (L + -2-methyl-3-(pyridin-2-yl)imidazo[1,5- a ]pyridinium cation), 20 we developed a convenient synthetic strategy to systematically modify the photoluminescent properties of imidazo[1,5- a ]pyridine species through varying substituents on the polyheterocyclic core as well as through introducing different metal ions. 21 The next cation in the series, 2-methylimidazo[1,5- a ]pyridinium, [L′] + , has been synthesized by the interaction between equimolar amounts of formaldehyde, methylamine hydrochloride and 2-pyridinecarbaldehyde (2-PCA) in an aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…Other different applications have been reported for multiimpy products such as bioimaging or therapeutic agents under UVA-LED irradiation conditions. [86][87][88] In this case, the tested products show a potential application as photodynamic therapy agents against tumour cells (F. Yagishita et al reported the use of UVA-LED λexc = 365 nm, 1.1 W as a light source). [86] In general, a multi-impy nucleus has been successfully prepared [89,90] showing similar chelating behaviours in compar-ison to the most investigated poly-pyridines or multibipyridines.…”
Section: Multi-impy Skeletonmentioning
confidence: 99%